Viabilidade de folículos ovarianos autotransplantados para o rim de camundongas Balb-C - Carmo, Nayara Almeida do (2013)
At birth , domestic animals exhibit a large stock of oocytes which only a minimum reaches meiotic maturation. These oocytes contained in primordial follicles are used for the development of studies in order to clarify issues related to the activation of primordial follicles and growth as well as promote the development of new contraceptive methods and new techniques for the recovery of fertility through its cultivation. Among the ovarian culture stands out in vivo , also known as transplantation, has as main objectives to promote the return of fertility in women undergoing treatment gonadotoxic and the preservation of genetic diversity of endangered animals. In this sense the research with the in vivo culture aims to determine which methodology seems more feasible and allows better maintenance and development of the transplanted tissue. Thus , this study aimed to assess the quality of ovarian follicles after transplantation under the kidney capsule of mice. For this, we used 10 female mice ( Mus musculus ) , divided into two groups , Group 1 : transplants removed after 15 days from the insertion of the fragment , group 2 after 30 days. It has been established the control group which are the ovarian cortical fragments removed directly for histological processing. Through evaluation by light microscopy , it was observed that there was a progressive reduction in the number of morphological normal follicles with progression of duration to 15 for 30 days of transplants. Regarding the number of normal preantral, only group 2 did not differ statistically from the control. The normal antral follicles in groups 1 and 2 did not differ but were significantly lower than the control group. Regarding the evaluation of apoptotic, we obtained a higher reaction to Caspase -3 in antral follicles in the three groups. According to the results obtained in this study, subcapsular renal autotransplantation technique has proved satisfactory for maintenance and study of preantral follicles